PENGARUH DIMENSI BUDAYA DAN RELIGIUSITAS TERHADAP KECURANGAN PAJAK - Yesi Mutia Basri (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
This research aims to analyze and get empirical evidence about theeffect of dimension of culture (Power Distance, Individualism, uncertaintyavoidance, masculinity) and religiouity on tax evasion. Population in this study isindividual tax payer listed in KPP Pratama Tampan Pekanbaru. Sampling technic isconvenience sampling. From 100 questioners distributed, 60 responden participated.The regression analysis results indicate power distance and masculinity affect havepositif effect on tax evasion, but higher religiosity has negatif effect on tax evasion.Finding indicate uncertainty avoidance and individualism have not significant effecton tax evasion.DOI: 10.15408/akt.v8i1.2764